دور اذاعة الاغواط في تنمية الثقافة الجمالية لدى المراة المحلية - حورية شقنان; د/ ذهبية ايت قاسي (جامعة عمار ثليجي الاغواط, 2024)
الملخص باللغة العربية: هدفت دراستنا إلى الوصول الى الإجابة عن الإشكالية التالية:هللبرنامج عالم الصباح (ركن التجميل) عبر اذاعة الجزائر من الاغواط دور في تنمية الثقافة الجماليةعند المرأة المحلية؟وذلك من خلال طرح الاسئلة الفرعية التالية أ‌. هل لبرنامج عالم الصباح (ركن التجميل) عبر اذاعة الجزائر من الاغواط دور في اكتساب المرأة عادات وأنماط وقيم جمالية عصرية؟ ب‌. هل لمواضيع برنامج عالم الصباح (ركن التجميل) عبر اذاعة الجزائر من الأغواط دور في زيادة دوافع استماع المرأة المحلية؟ وللوصول إلى اجابات شافية عن هذه الأسئلة إستخدمنا أداة الملاحظة وتقنية الإستبيان وخلال دراستنا الحالية انتهجنا المنهج الوصفي،ولتفريغ بياناتنا إحصائيا اعتمدنا على برنامج الحزم الاحصائية spss الإصداد 0.24 وقد توصلنا في الأخير الى ان الاذاعة المحلية لها دور كبير في نشر ثقافة الجمال وهذا من خلال نتائج الدراسة الميدانية التي أجريناها على مستوى ولاية الاغواط لبعض النساء المحليات اللواتي يتابعن برنامج عالم الصباح ركن التجميل ويطبقن الوصفات التجميلية بمقر عملنا. الكلمات المفتاحية: برنامج عالم الصباح (ركن التجميل)، اذاعة الجزائر من الاغواط، الثقافة الجمالية المرأة المحلية Summary in Arabic: Our study aimed to answer the following question: does the Alam Al-Sabah (Beauty Corner) program in Radio Algérie de Laghouat have a role in the development of the aesthetic culture of local women? This is done by asking the following sub-questions A. Does Laghouat's Radio Algérie program Alam Al-Sabah (Beauty Corner) have a role to . play in women's acquisition of modern aesthetic habits, styles and values B. Do the themes of the Alam Al-Sabah (Beauty Corner) program broadcast on Radio Algérie from Laghouat have a role in increasing the listening motivations of local women?To reach satisfactory answers to these questions, we used the observation tool and the questionnaire technique. During our current study, we adopted the descriptive approach, and to empty our data statistically, we relied on the statistical package program (SPSS), version 0.24. We finally concluded that local radio has a major role in spreading the culture of beauty, and this is through the results of the study. The field we conducted at the level of Laghouat state for some local women who follow the Alam Al-Sabah program, Beauty Corner, and apply cosmetic recipes at our workplace. Keywords: Alam Al-Sabah program (beauty corner), Radio Algeria from Laghouat, local women’s aesthetic culture
دراسة ميدانية على عينة من مستمعات برنامج " عالم الصباح ركن التجميل " باذاعة الاغواط